Mixed Methods Research online: Problems and Potential in Business Ethics Research - Issa, Theodora; Pick, David (IGI Global, 2015)
Contributing to the ongoing debate in research on sensitive issues such as business ethics, this chapter provides a discussion of mixed methods research design, examining the processes and challenges of developing and deploying an online survey tool using technology within an interpretive mixed methods design. This chapter provides pointers on how to deploy this approach through technology to research business ethics using the example of researching ethical mindsets and its components, including spirituality and aesthetics. It is found that mixed methods research is an effective approach because it allows often sensitive issues (i.e. business ethics, aesthetics, spirituality) relating to questing individuals' inner values and ethical propensities, which are usually subtle and difficult to measure and analyse constructs. While this tool was developed in the Australian context, it has the potential to form a foundation for wider examination and research in business ethics. The chapter contributes to the collective discussion of research methods using a framework that has both practical relevance and theoretical rigor.